The Effects of Influencer Follower Count on Consumer Perception and Purchase Behavior - Airavelle L. Abellana; Joseph P. Barbadillo; Dessa Kaye B. Basul; Aubrey Ann R. Castañares; Julia Fernanda S. Ceniza; Neil A. Dela Cruz; Lalaine O. Narsico; Peter G. Narsico (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
In this study, we analyze the influence of influencer follower count on purchase behavior and consumer perception in college students, and address an emerging gap in the social media-driven marketing research area. Influencers on the one hand have very different follower counts, credibility and knowledge on the other, and while little research has been done on how these factors affect consumers' responses. Based on digital consumer behavior and persuasion theory, we study three independent variables - follower count impact, consumer perception and purchase behavior - and how these predict consumer behavior. Using descriptive-correlational research design, we collected data from 394 college students through 5-point Likert scale surveys and the followers' characteristics (M = 3.49, Agree), consumer perception indicators (M = 3.09, Neutral) and purchase behavior (M = 3.40, Neutral). We found that the follower count impact is strongly correlated with consumer perception (R² = .43, F = 117.59, p < .001) and purchase behavior (R² = .49, F = 380.25, p < .001). Likewise, consumer perception influenced purchase behavior strongly (R² = .49, F = 380.25, p < .001). Furthermore, a study also demonstrated that influencer exposure and follower count shape purchase behavior directly and indirectly through consumer perception, which is the most important way to link influencer cues to buying behavior.